Pendapatan Asli Daerah, Dana Alokasi Umum, Dana Bagi Hasil Terhadap Pertumbuhan Ekonomi Kabupaten Boyolali - Aulia Noor Rohmah AlQomariah; Sri Laksmi Pardanawati; Wikan Budi Utami (Jurnal Ilmiah Keuangan Akuntansi Bisnis (JIKAB), 2022)
This study aims to determine the effect of regional original income, general allocation funds, profit sharing funds on economic growth in Boyolali Regency in 2017-2020. This research is a quantitative research using secondary data. The population and sample of this research is the 2017-2020 budget realization report, which consists of 84 data. Based on the results of the t-test that has been carried out, it can be seen that the regional original income partially has no significant effect on economic growth. General allocation funds have a significant effect on economic growth. profit sharing funds have a significant effect on economic growth. Based on the F test, it can be seen that local revenue, general allocation funds, profit sharing funds have a simultaneous effect on economic growth.